Comparison of Dose and Effectiveness of a Single-Session Ultrasound-Guided High-Intensity Focused Ultrasound Ablation of Uterine Fibroids With Different Sizes - Yang, Mei-Jie; Yu, Ren-Qiang; Chen, Jin-Yun; Wang, Zhi-Biao (Frontiers in Oncology, 2021)
Purpose: This study aimed to compare the dose and effectiveness of ultrasound–guided high–intensity focused ultrasound (USgHIFU) ablation of uterine fibroids with different sizes and explore the effect of uterine fibroid size on dose, which provided dose evaluation for clinicians in accordance with the size of uterine fibroids. Materials and Methods: A total of 1000 patients with symptomatic uterine fibroids who received a single–session USgHIFU treatment were enrolled in this study. The size of fibroids was divided into seven groups: 3–4 cm, 4–5 cm, 5–6 cm, 6–7 cm, 7–8 cm, 8–9 cm, and 9–11 cm. The dose was expressed on the basis of the energy efficiency factor (EEF) as the energy required for ablation per unit volume of tissue, and the non–perfused volume ratio (NPVR) was used to assess the effect of HIFU ablation. Results: The median NPVR of 88.3% (IQR: 80.3%–94.8%) was obtained, and no significant difference was observed among the seven groups. The classification of T2–weighted image signal intensity fibroids in the 4–5 cm group was compared with that in the 6–7 cm and 8–9 cm groups, and the difference was significant (P < 0.05). However, the proportion of T2WI hyperintense signal fibroids had no significant difference among the seven groups (P > 0.05). The median EEF was 3.88 J/mm3, and a significant difference was observed among the seven groups of EEF (P < 0.05). The EEF of groups with a fibroid size less than 6 cm was more than double the EEF of groups with a fibroid size above 6 cm. In addition, the EEF of groups with a fibroid size of 4–5 cm and 3–4 cm was 3–4 times higher than those with a fibroid size above 7 cm (P < 0.05). Conclusions: A single–session HIFU ablation for uterine fibroids of 3–11 cm can obtain a NPVR more than 80%. The EEF decreased with the increase of the size of uterine fibroids. Fibroid size of 6.5 cm was considered as a clinical meaningful point affecting EEF.